PENIAPHOBIA AS A COMPONENT OF THE DESTRUCTIVE DIGITAL MEDIA DISCOURSE IN THE ASIA-PACIFIC REGION - Margarita D. Lagutkina; Zhang Yi; Chang Thi Thu Huong (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
Modern hybrid linguistic-mental and information warfare massively uses the promotion of destruction in the mass media as a tool of negative ‘soft power’ media discourse directed against China, Vietnam and Russia owing to their being the key players in the geopolitical arena of Southeast Asia. The discourse of Western geopolitical opponents promotes peniaphobia (fear of poverty), which is one of the basic human fears since it is associated with ensuring the efficient viability of man and human civilization as a whole. The authors attribute peniaphobia to one of the universal social stigmas that affect the social structure and culture of the community, recognizing that media discourse is actively using open public Internet communication to control public consciousness gently. Meanwhile, intense exploitation by the media of alleged financial insolvency, looming economic crises, food shortages and impending hunger, the adverse effects of international labor migration and the deplorable state of the labor markets rapidly generate protest moods in society, changing social perceptions of money, food and food consumption. Information intakes that enhance peniaphobia use scenario modeling the presentation of potentially dangerous themes in the mass media of Russia, Vietnam and China. The article assesses the manipulation of public consciousness in the context of the pandemic, complicated by the psychological and informational confrontation between East and West and Western socio-economic and political sanctions imposed in connection with the Russian-Ukrainian conflict. Modern social culture has updated the features of presenting information using a digital format and subsequent decoding, which, in general, has influenced social dynamics. Based on analyzing the ethno- and sociocultural behavior of ‘digital aborigines’ on the Internet, the sociocultural approach to modern manipulation techniques of the public consciousness demonstrates the change in the use of methods of manipulation compared to representatives of the ‘pre-digital generation’.